Antioxidant Activity of Rosemary Extract in Soybean Oil Under Thermoxidation. Issue 1 (19th June 2012) - Casarotti, Sabrina Neves; Jorge, Neuza
ABSTRACT This study examined the antioxidant activity of lyophilized rosemary extract added to soybean oil, subjected to thermoxidation conditions and also its synergistic effect with the synthetic antioxidant tertiary butylhydroquinone (TBHQ). Soybean oil samples with no antioxidant added (SO), 3, 000 mg/kg rosemary extract (RE), 50 mg/kg TBHQ (TBHQ), and a mixture of those two antioxidants (RE + TBHQ) were heated to 180C for 20 h. After 0, 10 and 20 h, the oxidative stability, total polar compounds, tocopherol content and fatty acid profile were determined. The addition of rosemary extract increased oxidative stability and resulted in a lower formation of total polar compounds and a higher retention of tocopherols. The RE treatment showed the highest amount of polyunsaturated fatty acids after 20 h. There was not any synergy between TBHQ and rosemary extract in preventing oxidation of soybean oil. Rosemary extract showed a higher antioxidant potential when compared with TBHQ. PRACTICAL APPLICATIONS Antioxidants are important ingredients in food processing because they have the capacity to protect foods, containing oils and fats, from damage caused by free radicals and reactive oxygen species. Synthetic antioxidants are widely used in the food industry; however, their utilization has been questioned because of toxicity. Therefore, there is a growing interest in the use of natural antioxidants to reduce or replace the synthetic antioxidants. Several species are used in cooking, medicine and by the pharmaceutical industry, standing out the rosemary. Being rich in compounds with high antioxidant activity, the rosemary extract can be used to replace synthetic antioxidants used in vegetable oils.